Topical sterosomes-based nanocarrier of miconazole for the management of cutaneous candidiasis - Maha Alsunbul; Randa Mohammed Zaki; Ghaida N. Alnuwaybit; Fatimah A. Aljunayh; Mohd Nazam Ansari; Najeeb Ur Rehman; Abubaker M. Hamad; Fatma I. Abo El-Ela; Ehssan Moglad; Mayada Said (PLoS ONE, 2026)
Background Miconazole (MN) is widely used to treat superficial fungal infections; however, limited skin penetration and short residence time restrict its therapeutic efficacy. This study aimed to develop and statistically optimize MN-loaded sterosomes (STEs) to enhance topical antifungal activity. Methods A central composite rotatable design (CCRD) was applied using Design-Expert® software to study the effects of cholesterol amount (mg) and sonication time (min) on vesicle size (VS), zeta potential (ZP), and entrapment efficiency (EE%). Vesicle morphology was characterized by transmission electron microscopy (TEM), and drug entrapment was confirmed using X-ray diffraction (XRD). The optimized formulation was incorporated into a hydroxypropyl methylcellulose (HPMC) gel and evaluated for in vitro release and in-vivo antifungal efficacy in a Wistar albino rats cutaneous candidiasis model (n = 6) following topical administration of optimized MN-loaded sterosome gel 1% w/w for ten days. Results The optimized formulation showed a desirability of 0.63 and consisted of 140.86 mg cholesterol and 8.99 min sonication time. It demonstrated vesicle size: 498.54 ± 6.12 nm, zeta potential: 40.82 ± 1.24 mV, entrapment efficiency: 77.41 ± 1.43%. MN release from STEs was significantly higher than the drug suspension. TEM images showed spherical non-aggregated vesicles. XRD patterns indicated successful MN entrapment. In-vivo , MN-STE gel produced significantly greater antifungal activity than commercial Daktarin® cream at a lower dose, which was consistent with histopathological improvement. Conclusion MN-loaded sterosomes enhanced drug entrapment, release, and antifungal efficacy while enabling dose reduction, representing a promising carrier for topical miconazole delivery.